2007
DOI: 10.2105/ajph.2005.068437
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Condom Use at Sexual Debut and Subsequent Sexual Trajectories: A Longitudinal Study Using Biomarkers

Abstract: Adolescents who use condoms at their sexual debut do not report more sexual partners, are more likely to engage in subsequent protective behaviors, and experience fewer sexually transmitted infections than do adolescents who do not use condoms at their sexual debut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
2
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 35 publications
9
71
2
11
Order By: Relevance
“…Estudos realizados no Brasil e no mundo mostram que a vida sexual dos adolescentes tem início cada vez mais cedo e que a precocidade está associada ao sexo desprotegido e ao maior número de parceiros ao longo da vida 29 . A precocidade da primeira relação sexual pode trazer consequências graves para a saúde dos adolescentes.…”
Section: Discussionunclassified
“…Estudos realizados no Brasil e no mundo mostram que a vida sexual dos adolescentes tem início cada vez mais cedo e que a precocidade está associada ao sexo desprotegido e ao maior número de parceiros ao longo da vida 29 . A precocidade da primeira relação sexual pode trazer consequências graves para a saúde dos adolescentes.…”
Section: Discussionunclassified
“…There is some empirical evidence that the use of a condom in a person's first experience of sexual intercourse is a good predictor of continued use [6,7]. The possibility that condom use is habit-forming justifies the importance of targeting young people with health education campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the National Adolescent School-based Health Survey (PeNSE) in 2009, in the Brazilian capitals, showed that among adolescents aged 14 who have already had sexual intercourse, about more than a third (35.4%) had their first sexual intercourse when 12 years old or less, 42.3% among boys and 19.7% among girls 6 . Studies in Brazil 7,8 and in the world 4,5,9 show that early sexual intercourse is associated with unprotected sex and more partners over a lifetime. Unprotected sex is one of the factors which contribute the most to the increasing number of disability-adjusted life years (DALY) RESUMO: Objetivo: Este estudo descreve o comportamento sexual entre estudantes que participaram da Pesquisa Nacional sobre a Saúde do Escolar (PeNSE) 2012 e investiga se as desigualdades sociais, o uso de substâncias psicoativas e a presença de informações sobre a saúde sexual e reprodutiva na escola estão associados a diferenças nesse comportamento.…”
Section: Introductionmentioning
confidence: 99%
“…in adolescents and young adults 10 . The non-use or inappropriate use of condoms can lead to infections by sexually transmitted diseases (STDs) and pregnancy 4,5,9,11 . The high prevalence of STDs among Brazilian adolescents, such as chlamydia and HPV, is worrying 12 .…”
Section: Introductionmentioning
confidence: 99%